Perancangan Ontologi Semantik: Representasi Digital Gamelan Bali - I Gede Landip Anggareksa; I Komang Ari Mogi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
Balinese Gamelan, a traditional ensemble music from Bali, Indonesia, encompasses a rich cultural heritage. However, organizing and classifying its diverse musical compositions pose significant challenges. In this study, we propose an ontology-based semantic web approach for organizing and classifying Balinese Gamelan music. We develop an ontology that captures the hierarchical and relational structure of Gamelan music elements. Leveraging semantic web technologies, particularly RDF (Resource Description Framework) and SPARQL (SPARQL Protocol and RDF Query Language), we create a knowledge base that represents the ontology and facilitates efficient data retrieval and classification. Our approach provides a systematic and comprehensive framework for organizing and accessing Balinese Gamelan music information, offering a valuable resource for musicologists, researchers, and enthusiasts.